HBR guide to coaching employees. - Yen, Jonathan (Ascent Audio, 2022)
Help your employees help themselves. As a manager in today's business world, you can't just tell your direct reports what to do: You need to help them make their own decisions, enable them to solve tough problems, and actively develop their skills on the job. Whether you have a star on your team who's eager to advance, an underperformer who's dragging the group down, or a steady contributor who feels bored and neglected, you need to coach them: Help shape their goals-and support their efforts to achieve them. In the HBR Guide to Coaching Employees you'll learn how to: create realistic but inspiring plans for growth; ask the right questions to engage your employees in the development process; give them room to grapple with problems and discover solutions; allow them to make the most of their expertise while compelling them to stretch and grow; give them feedback they'll actually apply; and balance coaching with the rest of your workload. Arm yourself with the advice you need to succeed on the job, from a source you trust. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.